Methisoprinol (Inosine Pranobex) for Mumps During a Local Outbreak: Findings from a Descriptive Single-Center Study - Mujayanto, Rochman (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Mumps is an acute infectious disease caused by the paramyxovirus, commonly found in many countries. In 2024, mumps outbreaks were reported globally, with significant cases in India (18,158), the USA (328), the Netherlands (578), and Indonesia (413). The current treatment guidelines for mumps are paracetamol or ibuprofen for pain relief. Purpose: To describe clinical profiles and outcomes of mumps patients treated with methisoprinol in a single-center cross-sectional study. Methods: A descriptive cross-sectional study of mumps patients treated with methisoprinol was conducted at the Islamic Dental Hospital Sultan Agung, Semarang, using retrospective data from August to December 2024. Mumps was defined by the WHO's clinical definition of parotid gland swelling. Results: Among 35 mumps patients, there was an almost equal gender distribution, with most being under 18. The majority had a history of febrile illness, used symptomatic medication, and lacked MMR vaccination history. There was a significant difference in the duration of parotitis before and after methisoprinol medication. Factors like sex, age, parotitis location, and MMR vaccination history did not significantly affect recovery time. Conclusion: Methisoprinol significantly reduced the duration of parotitis, while sex, age, parotitis location, and MMR vaccination history did not significantly influence recovery time.